Immediate Postpartum Glucose Tolerance Testing in Women with Gestational Diabetes: A Pilot Study - Dinglas, Cheryl; Muscat, Jolene; Heo, Hye; Islam, Shahidul; Vintzileos, Anthony (American Journal of Perinatology, 2017)
Objective Due to poor adherence for glucose testing at 6- to 12-week postpartum among women with gestational diabetes, we sought to determine whether a 2-hour glucose tolerance test (GTT) during postpartum hospitalization is predictive of 6- to 12-week postpartum glucose testing.Study Design An institutional review board–approved prospective cohort study was performed over 3 years. Patients underwent an inpatient fasting 75-g, 2-hour GTT on either postpartum days 2 through 4 and instructed to follow up in 6- to 12-weeks for postpartum glucose testing. Sensitivity, specificity, positive predictive value (PPV), and negative predictive values (NPV) of the immediate GTT to predict abnormal 6- to 12-week postpartum glucose testing were determined.Results Eighty women enrolled in the study completed the immediate GTT; of these, only 35 (44%) underwent 6- to 12-week postpartum glucose testing. The sensitivity, specificity, PPV, and NPV of the immediate GTT were 100, 42.8, 30.4, and 100%, respectively.Conclusion More than 50% of our study patients did not undergo recommended postpartum glucose testing, coinciding with similar poor follow-up reported in the literature. With a high NPV and high sensitivity, a negative immediate GTT may obviate the need for the 6- to 12-week GTT, while a positive GTT may identify women who should follow up closely.
Keywords: gestational diabetes; glucose tolerance test; glucose intolerance; postpartum testing